Fazendeiros, negros e imigrantes em Castello (1891-1928): processo histórico de poder territorial no sul do Espírito Santo - Gomes, Ademildo (2023)
The doctoral thesis proposes to study the relationship between farmers, blacks and immigrants in the Estação do Castello district, in the southern region of Espírito Santo, between 1891 and 1928, with the historical process of land acquisition as the epicenter of the research. The current Municipality of Castello, after a sparse colonization caused by mining, was formed from the large farms established in its territory in the 19th century. The farms, made up of large tracts of land, had coffee cultivation and the slave regime as their productive foundations. With the abolition, on May 13, 1888, and the devaluation of coffee, starting in 1896, a gradual process of access to land was opened, in which the large estates, little by little, were transformed into small properties. In this process stood out the landowners and their heirs, the freed blacks with their families, and the immigrants and their descendants. All recognizing in the land a symbol of power. The object of the research is based on these groups, with a view to analyzing their different implemented power strategies and the possibilities they had to access the land in the Castello district. The text follows the methodological perspective of micro-history, giving preference to local history, but not dissociating itself from general history. Therefore, it is presented as a microanalysis that allows us to glimpse some elements of the political dynamics experienced in Brazil in the postabolition period. The sources are mainly composed of five sets, namely: reports and messages from the governments of Espírito Santo; the land documents of the Agriculture and Governance Fund of the Public Archive of the State of Espírito Santo; notary records (post-mortem inventories, civil birth records and property deeds); ecclesiastical documents, especially the baptism records of the Parish of São Pedro de Cachoeiro de Itapemirim and of the Parish of Nossa Senhora da Conceição of Conceição do Castelo; the press sources, especially the newspapers from the south of Espírito Santo, the Cachoeirano and the Constitucional, examined according to discourse analysis. It was found that, after abolition, the myth of racial hierarchy and the whitening policy favored immigrants and made the black population invisible in terms of participation in the process of acquiring land as owners, in addition to reaffirming racism, distancing the relationship between these two ethnic groups.